2020
DOI: 10.1155/2020/3517104
|View full text |Cite
|
Sign up to set email alerts
|

Combination of D-AHP and Grey Theory for the Assessment of the Information Security Risks of Smart Grids

Abstract: As a modern power infrastructure, smart grids have great advantages over traditional power grids, but their effective operation is largely restricted by information security. Hence, a smart grid information security risk assessment (ISRA) method is proposed. This method combines D numbers to improve the classical analytic hierarchy process (D-AHP) independent of experts’ subjective qualitative assessment and then integrated with grey theory which does not require complete and unambiguous information. First, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The results showed that the proposed technique could potentially increase the reliability of network security risk assessments. Dong et al [56] used a modified AHP called D-AHP to evaluate security of smart grids. The top-level criteria used included smart terminal, wireless communication channel, password security, application code and the embedded system.…”
Section: A Using Ahp To Assess Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the proposed technique could potentially increase the reliability of network security risk assessments. Dong et al [56] used a modified AHP called D-AHP to evaluate security of smart grids. The top-level criteria used included smart terminal, wireless communication channel, password security, application code and the embedded system.…”
Section: A Using Ahp To Assess Securitymentioning
confidence: 99%
“…), management (safety management, etc.) [54] Security Level Agreements Compliance, data governance, information security Network Security [55] Network Security Assets, access control, communication [56] Smart Grid Security Smart terminal, wireless channel, password security, app. code, embedded system [57] Network Security Software, hardware, information, communication, organization, physical environment [58] Wireless Security Authenticity, availability, confidentiality, integrity, non-repudiation theory to assess wireless network security using the top-level criteria of authenticity, availability, confidentiality, and integrity.…”
Section: A Using Ahp To Assess Securitymentioning
confidence: 99%
“…Password guessing is a method of gaining access to a system by guessing passwords and gaining access to a targeted device. In addition, the attacker consumes network resources and bandwidth to carry out several attacks that consequently limit the access of legitimate users to the resources [147].…”
Section: Password Strengthmentioning
confidence: 99%
“…Step 4. The preference probability used to represent the pairwise comparison indices was the probability matrix R P constructed by the crisp matrix R C [50]. The elements in the matrix were recorded as c ij , while the elements in the matrix R P were denoted as p ij = Pr U i > U j , ∀i, j ∈ {1, 2, .…”
Section: D-number Theorymentioning
confidence: 99%